Clinical spectrum of dengue in pediatric age group: A study at tertiary care hospital - Mehta, Kirti; Patel, Avani; Patel, Priti P; Patel, Ankur (Indian Journal of Child Health, 2020)
Background: Dengue is a mosquito-borne human viral disease, which has become a major public health problem recently. The clinical manifestation of dengue infection varies from asymptomatic to severe fatal condition in the form of dengue hemorrhagic fever/dengue shock syndrome. Objectives: The objectives of this study were to study the clinical profile and hematological changes in dengue fever. Materials and Methods: This prospective observational study was carried out at a tertiary care hospital from March 2017 to August 2018. The study population included dengue positive patients admitted to the pediatric ward. All the children age up to 12 years with positive dengue test either NS1 antigen or IgM/IgG antibodies by rapid serological test kit or ELISA were included in the study. Results: Of 105 cases, the most common clinical feature was fever (100%) with raised hematocrit value (45.8%), leukopenia (38.1%), and thrombocytopenia (74%). Conclusion: Hematological profile with thrombocytopenia, raised hematocrit, and leukopenia with raised serum glutamic-pyruvic transaminase gives enough clues to test for dengue serology to reduce the morbidity and mortality by early diagnosis and management of dengue illness.